2014
DOI: 10.1371/journal.pone.0091444
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study on Meckel Cave with Endoscopic Endonasal, Endo-Maxillary Sinus, and Endo-Pterygoid Process Approaches

Abstract: ObjectiveTo study anatomical structures related to Meckel cave with endonasal endoscopic approach and to provide an anatomical basis for endoscopic surgery in Meckel cave.MethodsMeckel cave of 5 adult skulls (10 sides) were fixed with 10% formalin. The anatomical structures of Meckel cave and the related zones adjacent to Meckel cave were observed and measured with endoscopic endonasal approach.ResultsEndoscopic endonasal, endo-maxillary sinus, and endo-pterygoid process approaches were successfully applied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…ESS‐assisted pterygoid process approach was recommended due to the challenges posed by the presence of closely situated vital structures such as the optic nerve and the carotid artery . Although one study has suggested that endonasal pterygoid process approach could take advantage of the vidian nerve to locate the position of foramen lacerum of the internal carotid artery, another study has set up a classification to help to understand anatomy of pterygoid area to achieve endoscopic endonasal transpterygoid approach . In this study, 9 tumors were found to break through the sphenoid sinus septum and invade bilateral sphenoid sinus (stage 3, Supporting Information Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…ESS‐assisted pterygoid process approach was recommended due to the challenges posed by the presence of closely situated vital structures such as the optic nerve and the carotid artery . Although one study has suggested that endonasal pterygoid process approach could take advantage of the vidian nerve to locate the position of foramen lacerum of the internal carotid artery, another study has set up a classification to help to understand anatomy of pterygoid area to achieve endoscopic endonasal transpterygoid approach . In this study, 9 tumors were found to break through the sphenoid sinus septum and invade bilateral sphenoid sinus (stage 3, Supporting Information Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…These include frontotemporal (3), anterolateral (1), and lateral (middle fossa) approaches (4), with variations in craniotomy and intracranial bone removal based on specific tumor characteristics. More recently, endoscopic (57) and radiosurgical (8) strategies have also emerged as promising modes of therapy for certain tumors. Common to any open surgical approach is the need to gain the most direct route of access to the lesion, provide the exposure necessary to maximize tumor resection, minimize brain retraction, and afford vascular control.…”
Section: Introductionmentioning
confidence: 99%